(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The objective of the present study was to evaluate step length of middle-aged adults and older adults. Ten adults (14 middle age adults and 14 older adults) were recruited from a local community. They were all physically healthy and not injured in the last 6 months. One marker was placed on each heel (right and left heels) and the position data were collected during subsequent 5-minute walking on a straight track (15m long). The results indicated that step length of middle-age adults were larger than that of older adults during their natural gait. The study concluded that middle-age adults would likely to be involved in slips and falls.